Neisseria gonorrhoeae antimicrobial resistance in Manaus: 2005-2006 period - Ferreira, William A; Vasconcelos, Waldemara S; Silva, Maria de Fátima P; Gomes, Jairo S; Ferreira, Cristina M; Benzaken, Adele S (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: in 1998, the Alfredo da Matta Foundation from Manaus launched studies to evaluate the resistance of N. gonorrhoeaestrains to the anti-biotics penicillin, tetracycline, azithromycin, ceftriaxone and ciprofloxacin. Objective:checking the resistance of isolates of Neisseria gonorrhoeaetothe antibiotics penicillin, tetracycline, azithromycin, ceftriaxone and ciprofloxacin in the Clinic Bacteriology Laboratory from Alfredo da Matta foun-dation, Manaus - Amazonas - Brazil. Methods:in this study, the resistance of 110 strains was evaluated by the disc diffusion method. Results:thetests showed that 14,5% of the isolates were â-lactamase positive (PPNG) and the resistance to the penicillin was 21,8%. For the tetracycline, 80,0%were resistant with 12,7% TRNG. In relation to azithromycin, 8,2% of the gonococci were resistant. To the ciprofloxacin, 6,4% of the strains showedreduced sensibility and with the use of ceftriaxone, 5,5% of the isolates had a diameter inferior to 33 mm in the susceptibility test. Conclusion:the con-clusion is that the high percentages of resistance to the penicillin and tetracycline are similar to other studies done with the strains this region and sug-gest that the selective pressure on those antibiotic continues is high. The resistance levels for azithromycin make it unfeasible to be used as a therapeu-tic method. Resistance to from ciprofloxacin and ceftriaxone was mpt detected but the percentage of reduced sensibility for the ciprofloxacin and thestrains with a diameter below 35 mm in the disc diffusion susceptibility test for the ceftriaxone, suggest that constant clinical and laboratorial surveil-lance is necessary.